(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
In this article we study about performance of gas turbine. The industrial gas turbines demonstrate output results that rely distinctly on atmospheric and operational conditions. Not only site height, air temperature, affects them. And relative temperature, but also the speed of the machinery being powered, the fuel and the load conditions. Applying gas turbines correctly needs analysis of certain variables. This guide describes certain features centered on the engine compressor output. Part of the combustor and generator, and other regulation methods. It introduces simple concepts which help to understand the energy flow between the components. Therefore. Methods are implemented which allow data to be used for trend and comparison purposes. The effect of component deterioration on the efficiency of individual components and overall engine output was addressed, along with approaches to reduce the influence of deterioration.